Out of sight, out of mind? On the risk of sub-custodian structures - Thomas Droll; Natalia Podlich; Michael Wedow (Deutsche Bundesbank, 2015)
We analyse sub-custodian chains using a unique data set from a survey. Our key question is whether there is any evidence for moral hazard in the delegation of asset safe-keeping to sub-custodians. Sub-custodian chains can be relatively long and frequently reach across several countries. The risk that securities are lost or the return to their owners delayed is not negligible. Our findings highlight that foreign or better informed banks have shorter sub-custodian chains. Better capitalised banks have longer, but less risky sub-custodian chains. Our findings support the view that Central Securities Depositories (CSDs) play a beneficial role in the management of sub-custodian structures, since chains where a CSD is the first sub-custodian reduce the country risk in sub-custodian structures. When we analyse the choice of a CSD as first sub-custodian, we find that better capitalised, larger and foreign banks are less likely to rely on CSDs as their first sub-custodian.
Keywords: G14; G21; G28; 330; Custodian Banks; UCITS funds; Moral Hazard